Diurnal variations of fossil and nonfossil carbonaceous aerosols in Beijing. (December 2015) - Morino, Y.; Ohara, T.; Xu, J.; Hasegawa, S.; Zhao, B.; Fushimi, A.; Tanabe, K.; Kondo, M.; Uchida, M.; Yamaji, K.; Yang, L.; Song, S.; et al.
Abstract: For the source apportionment of carbonaceous aerosols, measurement of 14 C is an effective technique. In particular, diurnal variations of fossil and nonfossil carbonaceous aerosols provide information about the sources and production pathways of elemental carbon (EC) and organic carbon (OC). In this study, concentrations of fine-mode aerosols, including EC, OC, and 14 C, were observed with a time resolution of 6 h near the urban center of Beijing in June 2010. The observations indicate that the contribution of fossil secondary organic aerosol (SOA) increased during daytime. This finding is consistent with previous studies in other urban sites, suggesting that SOA production from anthropogenic sources is important in urban areas. We evaluated the performance of two chemical transport models (CTMs) with different SOA models on simulations of EC and OC. Both models well reproduced the concentration and diurnal variation of EC. OC concentrations were underestimated by more than half by the CTM with a SOA yield model, and were better reproduced by the CTM with a volatility basis set (VBS) model. However, even the VBS model underestimated both fossil and nonfossil total carbon (EC + OC), and possible reasons for this underestimation are discussed. Highlights: Diurnal variations of fossil and nonfossil total carbon were observed in Beijing. Contribution of fossil secondary organic aerosol (SOA) increased in daytime. This diurnal behavior was consistent with previous studies in other urban sites. Organic carbon was better reproduced by a VBS model than by a SOA yield model.